Investigating the mediating role of psychological safety and workplace belonging in the relationship between inclusive leadership and employee engagement - Mamogale, Basetsana (School of Management Studies, 2025)
The world of work has embraced remote working since the beginning of the pandemic, in some industries certain employees are able to work remotely full time. However, how does the concept of inclusive leadership and its key mechanisms such as facilitating belonging and valuing uniqueness impact employee engagement. Therefore, this study aimed to find the how psychological safety as the ability for inclusive leaders to show that they value uniqueness within their employee. The study also aimed to see if leaders can create a sense of belonging within their followers, this was taken from the Randel et al., 2018 framework of inclusive leadership, of how the mechanisms of sense of belonging and valuing uniqueness is the makeup of inclusive leaders. A simple regression analysis and mediation analysis was used to answer the research questions. It was found that there is a predictive relationship between inclusive leadership and employee engagement. Also, the workplace belonging mediated the relationship between inclusive leadership and employee engagement, but psychological safety does not mediate the relationship inclusive leadership and employee engagement.